(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Migraine is a debilitating neurological condition, which can be categorized into episodic and chronic groups based on its clinical pattern. Avoiding the risk factors exacerbating migraine is not enough to reduce the frequency and severity of migraine headaches, and in the case of non-receiving proper drug treatment, episodic migraines have the potential to become chronic, which increases the risk of cardiovascular complications and leaves great impact on the quality of life of patients and increasing the health-care costs. The objective of this research was to compare the effects of venlafaxine (VFL) and nortriptyline and propranolol in preventing migraines. Methods: This research is an interventional study performed on 60 patients with migraine admitted to the neurological clinic. Patients were visited at 3 time intervals. In each stage, the variables of headache frequency, headache severity, nausea, vomiting, and drowsiness were recorded. Data were analyzed using SPSS 23 software. Results: VFL drug with a daily dose of 37.5 mg is not only more tolerable in the long term but also leaves better effect in reducing the frequency and severity of headaches compared to the combination of nortriptyline and propranolol. Conclusion: VFL is an appropriate, effective, and tolerable alternative to migraine treatment.